Predictors of delayed Anti-Retroviral Therapy initiation among adults referred for HIV treatment in Uganda: a cross-sectional study - Micheal Kiyingi; Joaniter I. Nankabirwa; Christine Sekaggya-Wiltshire; Joan Nangendo; John M. Kiweewa; Anne R. Katahoire; Fred C. Semitala (BMC, 2023)
Abstract Background Uganda's current guidelines recommend immediate initiation of Anti-Retroviral Therapy (ART) for persons living with HIV in order to reduce HIV/AIDS related morbidity and mortality. However, not all eligible PLHIV initiate ART within the recommended time following HIV diagnosis. We assessed the prevalence and factors associated with delayed ART initiation among PLHIV referred for ART initiation, five years since rolling out the test and treat guidelines. Methods In this cross-sectional study, we enrolled adult patients referred to Mulago Immune Suppressive Syndrome (Mulago ISS) clinic for ART initiation from January 2017 to May 2021. We collected data on socio-demographics, HIV diagnosis and referral circumstances, and time to ART initiation using a questionnaire. The outcome of interest was proportion of patients that delayed ART, defined as spending more than 30 days from HIV diagnosis to ART initiation. We performed multivariable logistic regression and identified significant factors. Results A total of 312 patients were enrolled of which 62.2% were female. The median (inter-quartile range [IQR]) age and baseline CD4 count of the patients were 35 (28-42) years and 315 (118.8-580.5) cells/μL respectively. Forty-eight (15.4%) patients delayed ART initiation and had a median (IQR) time to ART of 92 (49.0-273.5) days. The factors associated with delayed ART initiation were; 1) having had the HIV diagnosis made from a private health facility versus public, (adjusted odds ratio [aOR] = 2.4 (95% confidence interval [CI] 1.1-5.5); 2) initial denial of positive HIV test results, aOR = 5.4 (95% CI: 2.0-15.0); and, 3) having not received a follow up phone call from the place of HIV diagnosis, aOR = 2.8 (95% CI: 1.2-6.8). Conclusion There was significant delay of ART initiation among referred PLHIV within 5 years after the rollout of test and treat guidelines in Uganda. Health system challenges in the continuity of HIV care services negatively affects timely ART initiation among referred PLHIV in Uganda.